THE EDIACARA BIOTA: NEOPROTEROZOIC ORIGIN OF ANIMALS AND THEIR ECOSYSTEMS - Narbonne G.M. (My University, 2005)
The Ediacara biota (575–542 Ma) marks the first appearance of large, architecturally complex organisms in Earth history. Present evidence suggests that the Ediacara biota included a mixture of stem-and crown-group radial animals, stem-group bilaterian animals, "failed experiments" in animal evolution, and perhaps representa-tives of other eukaryotic kingdoms. These soft-bodied organisms were preserved under (or rarely within) event beds of sand or volcanic ash, and four distinct preservational styles (Flinders-, Fermeuse-, Conception-, and Nama-style) profoundly affected the types of organisms and features that could be preserved. Even the earliest Ediacaran communities (575–565 Ma) show vertical and lateral niche subdivision of the ses-sile, benthic, filter-feeding organisms, which is strikingly like that of Phanerozoic and modern communities. Later biological and ecological innovations include mobility (>555 Ma), calcification (550 Ma), and predation (<549 Ma). The Ediacara biota abruptly disappeared 542 million years ago, probably as a consequence of mass extinc-tion and/or biological interactions with the rapidly evolving animals of the Cambrian explosion.
Keywords: Neoproterozoic; Precambrian::Proterozoic::Neoproterozoic